“The Analog Republic” and the vicissitudes of the Montecristi Constitution - Arcentales Illescas, Javier (2020)
The play “The Analog Republic” of the playwright Arístides Vargas, proposes a story about the creation of an utopian society that allows us to place correspondences with the contents of the Montecristi Constitution and with the avatars in the search for its materialization. In this search two key issues have been put into play, such as the State model and the visibility of diversity in the constitutional text. All these debates sustained by the horizon of a just society that has as an antagonist the disagreements of those who participate in the attempt without valuing it.